2008
DOI: 10.1111/j.1708-8208.2007.00056.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Surface Properties of Commercially Available Dental Implants Using Scanning Electron Microscopy, Focused Ion Beam, and High‐Resolution Transmission Electron Microscopy

Abstract: This indicates that the provision of osseointegration is not exclusively linked to a particular set of surface features if the implant surface character is a major factor in that process. The studied methodology provides an effective tool to also analyze the interface between implant and surrounding bone. This would be a natural next step in understanding the ultrastructure of the interface between bone and implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
1
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 19 publications
6
55
1
5
Order By: Relevance
“…Recently, focused ion beam (FIB) milling was used to prepare cross sections of dental implants and the tissue/implant interfaces. It has been proven a promising method for preparing cross sections without mechanical impact on the sample for electron microscope characterization, particularly for transmission electron microscopy (TEM) observation [8][9][10][11]. The limitation of FIB is the fact that the polished area is rather small, typical about 20 μm in edge lengths, which only cover one or two pores in case of the oxidized titanium implants.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, focused ion beam (FIB) milling was used to prepare cross sections of dental implants and the tissue/implant interfaces. It has been proven a promising method for preparing cross sections without mechanical impact on the sample for electron microscope characterization, particularly for transmission electron microscopy (TEM) observation [8][9][10][11]. The limitation of FIB is the fact that the polished area is rather small, typical about 20 μm in edge lengths, which only cover one or two pores in case of the oxidized titanium implants.…”
Section: Introductionmentioning
confidence: 99%
“…Elements of Ti, O, C and a small amount of P were present on the TiUnite  implant surfaces. Previous studies have shown this to be a characteristic feature of these implants, insofar as P is incorporated into an anodic titanium oxide layer 8,9 to stimulate bone regeneration and increase the biochemical interlocking between bone matrix proteins and surface materials, thus improving osseointegration. 2 EDS analysis of the paste, before usage, showed predominantly high elements of Al and Si, and was used to compare the paste composition to that of the implants after exposure to Expasyl  for elemental identification.…”
Section: Surface Topographymentioning
confidence: 99%
“…These processes create micropits superimposed on the rough-blasted surface. Jarmar et al measured the roughness on SLA TM and found it to be 1.98 ± 0.08 μm (Jarmar et al, 2008). Another way Wennerberg et al (Wennerbeg et al, 2003) verified that SLA TM implant has Sa = 1.42 m, waviness parameter S cx = 16.60 m and the surface parameter S dr increased 33%.…”
Section: Sandblasting Surface Treatmentmentioning
confidence: 92%